2003
DOI: 10.1179/oeh.2003.9.3.206
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Mesothelioma in Australia, 1945–2002

Abstract: Using register data, time trends in mesothelioma incidence in Australia from 1945 to 2002 were calculated. Incidences are reported by age, sex, anatomic site, and state of notification. Associations with occupational and environmental asbestos exposure histories and lifetime risks in different exposure categories were investigated. Lung-fiber content was measured in a subset of cases. Australia had 7,027 cases from 1945 to 2001, with 488 more in January 2002 through June 2003. Incidence rates for Australia per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
115
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 29 publications
8
115
0
1
Order By: Relevance
“…UK amosite imports were 21 600 tonnes (0.4 kg per head) in 1970 and did not decline until after 1976, while US amosite imports fell from 12 900 tonnes (0.07 kg per head) in 1970 to 1 400 tonnes in 1976 (MRC Institute for Environment and Health, 1997;Virta, 2006). Australia's mesothelioma death-rates are similar to Britain's, and so were its patterns of amosite and crocidolite use (Leigh and Driscoll, 2003).…”
Section: Contribution Of Amositementioning
confidence: 86%
“…UK amosite imports were 21 600 tonnes (0.4 kg per head) in 1970 and did not decline until after 1976, while US amosite imports fell from 12 900 tonnes (0.07 kg per head) in 1970 to 1 400 tonnes in 1976 (MRC Institute for Environment and Health, 1997;Virta, 2006). Australia's mesothelioma death-rates are similar to Britain's, and so were its patterns of amosite and crocidolite use (Leigh and Driscoll, 2003).…”
Section: Contribution Of Amositementioning
confidence: 86%
“…Several studies have shown an increasing incidence of this disease, which has probably already peaked in the United States, and is predicted to peak in Europe between 2010 and 2020 (1,2). Australia had heavy asbestos usage in the 1950s and 1960s, and one report has predicted a total of 18 000 malignant mesothelioma cases by 2020 (3,4).…”
mentioning
confidence: 99%
“…In Australia, cases among women have been reported to account for approximately 19% of the total cases (13). Due to relatively small numbers and difficulties in obtaining accurate data, few previous studies have assessed gender differences, and most do not distinguish between genders or have sufficient occupational data to comment on asbestos exposure (14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Incidence calculated projections suggest a peak in men around 2017 in the Netherlands, around 2014 in Australia and between 2011 and 2015 in Great Britain. [8][9][10][11][12] Nevertheless, mesothelioma incidence in men in the United States and in the population of Sweden seems to have levelled off in the 1990s. [13][14][15][16][17] In Finland, a reduction of the incidence increase was also noted in the early 1990s.…”
mentioning
confidence: 99%